RITUAL ARUWAHANG PADA ORANG TERNATE DI TOGOLOBE, PULAU HIRI - ASRUL LAMUNU; SAFRUDIN ABD. RAHMAN; DEWI APRIANI ACO (ETNOHISTORI: Jurnal Ilmiah Kebudayaan dan Kesejarahan, 2020)
Ternate is an historical Sultanate with a variety of cultures and traditions. An example of this is the Aruwahang death rite of the ethnic Ternate people of Togolobe, Hiri island. The people of Ternate also have a rich oral tradition, which is still practised today. Ethnic Ternate people uphold these adat (customary) norms and values. The wealth of these traditions serves as evidence that Ternate is a region capable of conserving its ancestral culture as well as giving meaning to the norms and values there of. In order that the meaning of the Aruwahang ritual be fulfilled, it is considered important that it be performed with strong adherence to customary procedure. Ternate people do not consider the Aruwahang to be merely a ceremonial procession, but as an essential ritual after a person’s death. The followers of the Aruwahang believe in the value and meaning that this ritual gives to the people of Ternate. The place the ritual takes place, the attendees (gogoro), the offering of adat food (ngogu adat), and other aspects of the ritual, are all considered to have an important meaning with regards to the life of an ethnic Ternate person. Ngogu adat, usually called jaha se kukusan by the local people, is based upon symbols of life, death and faith in God. This study was conducted in Togolobe village, Hiri Island sub-district, North Maluku. Qualitative data were collected from observation, in-depth interviews, and other technical documentation provided by the study subjects. The study was conducted in four stages: study design, data collection, data analysis, and presentation of results. The data analysis was performed in three stages: data reduction, data display, and conclusion drawing and verification. Two principal conclusions were derived from our study. Firstly, the Aruwahang ritual is an attractive and unique ancestral inheritance that must be maintained by the ethnic Ternate people. Secondly, that Aruwahang is a religious death rite (dina) that is still faithfully practiced today. Kata kunci: Aruwahang ritual, ngogu adat, dina, symbolism